Traversing the bench to bedside journey for iNKT cell therapies - O’Neal, Julie; Mavers, Melissa; Jayasinghe, Reyka G.; DiPersio, John F. (Frontiers in Immunology, 2024)
Invariant natural killer T (iNKT) cells are immune cells that harness properties of both the innate and adaptive immune system and exert multiple functions critical for the control of various diseases. Prevention of graft versus host disease (GVHD) by iNKT cells has been demonstrated in mouse models and in correlative human studies in which high iNKT cell content in the donor graft is associated with reduced GVHD in the setting of allogeneic hematopoietic stem cell transplants. This suggests that approaches to increase the number of iNKT cells in the setting of an allogeneic transplant may reduce GVHD. iNKT cells can also induce cytolysis of tumor cells, and murine experiments demonstrate that activating iNKT cells in vivo or treating mice with ex vivo expanded iNKT cells can reduce tumor burden. More recently, research has focused on testing anti-tumor efficacy of iNKT cells genetically modified to express a chimeric antigen receptor (CAR) protein (CAR-iNKT) cells to enhance iNKT tumor killing. Further, several of these approaches are now being tested in clinical trials, with strong safety signals demonstrated, though efficacy remains to be established following these early phase clinical trials. Here we review the progress in the field relating to role of iNKT cells in GVHD prevention and anti-cancer efficacy.Although the iNKT field is progressing at an exciting rate, there is much to learn regarding iNKT cell subset immunophenotype and functional relationships, optimal ex vivo expansion approaches, ideal treatment protocols, need for cytokine support, and rejection risk of iNKT cells in the allogeneic setting.